The main factors of efficiency of modern enterprise management - Fu Lin (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
Object of research The object of research is the management efficiency of China Changcheng Trust Company Limited, focusing on analyzing its operational efficiency, exploring ways to improve it, and examining the impact of controlling mechanisms on enhancing enterprise management efficiency. Subject of research is the comprehensive analysis and improvement of the management efficiency of China Changcheng Trust Company Limited, with a focus on strategic, operational, and controlling aspects. Purpose of qualification master's work the purpose of this master's work is to provide a comprehensive analysis of the factors influencing the management efficiency of China Changcheng Trust Company Limited, to identify areas for improvement, and to propose strategies that can lead to increased efficiency and competitiveness based on both internal strengths and external opportunities. According to results of the research, the results of the research indicate that while China Changcheng Trust Company Limited has shown strengths in areas such as strong shareholder support and initial success in new business areas, it also faces challenges like high operating costs and reputational issues.
Основні чинники ефективності управління сучасним підприємством
Scientific adviser: Hnyp Nataliia, PhD in economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; management efficiency; trust company; strategic control; operational optimization